The costume designer's handbook : a complete guide for amateur and professional costume designers - Ingham, Rosemary (Waveland Press, 2024)
"The Costume Designer's Handbook is the definitive guide for both aspiring and seasoned costume designers, blending the art and business of theatrical costume design since its inception in 1983. Rosemary Ingham and Liz Covey offer deep insights into play analysis, historical research, collaboration techniques, drafting, and setting up an effective workspace. The book addresses the practicalities of the industry, including job market navigation, freelancing, contracts, and taxes. With over 150 illustrations, an 8-page color insert, and a comprehensive reference section for resources, this handbook encapsulates the essence of costume design, making it an indispensable resource for professionals in the field."